2014
DOI: 10.1111/gcb.12583
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting long‐term records of biomass burning in wet and dry savannas of equatorial East Africa

Abstract: Rainfall controls fire in tropical savanna ecosystems through impacting both the amount and flammability of plant biomass, and consequently, predicted changes in tropical precipitation over the next century are likely to have contrasting effects on the fire regimes of wet and dry savannas. We reconstructed the long-term dynamics of biomass burning in equatorial East Africa, using fossil charcoal particles from two well-dated lake-sediment records in western Uganda and central Kenya. We compared these high-reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 59 publications
(97 reference statements)
4
40
1
Order By: Relevance
“…Indeed, a reduction in macroscopic‐CHAR was also observed in New Zealand following pyrophobic forest removal, where there was a decline in biomass availability following burning and deforestation after the Maori (McWethy et al, ). Further afield, our data showing high charcoal accumulation in line with high forest cover are analogous to studies from Kenya (Colombaroli et al, ), Spain (Gil‐Romera et al, ), and Arizona (Brunelle et al, ), where biomass limitation was indicated as the most plausible explanation for the link between high forest cover and high charcoal influx. Nevertheless, the hypothesis of biomass‐limited fire occurrence is unlikely in the generally high biomass environments of western Tasmania (McWethy et al, ); thus, it is more likely that a variation in the fuel type, from rainforest to sclerophyll vegetation, would have modulated charcoal influx in the Dove Lake record.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, a reduction in macroscopic‐CHAR was also observed in New Zealand following pyrophobic forest removal, where there was a decline in biomass availability following burning and deforestation after the Maori (McWethy et al, ). Further afield, our data showing high charcoal accumulation in line with high forest cover are analogous to studies from Kenya (Colombaroli et al, ), Spain (Gil‐Romera et al, ), and Arizona (Brunelle et al, ), where biomass limitation was indicated as the most plausible explanation for the link between high forest cover and high charcoal influx. Nevertheless, the hypothesis of biomass‐limited fire occurrence is unlikely in the generally high biomass environments of western Tasmania (McWethy et al, ); thus, it is more likely that a variation in the fuel type, from rainforest to sclerophyll vegetation, would have modulated charcoal influx in the Dove Lake record.…”
Section: Discussionsupporting
confidence: 89%
“…Macroscopic charcoal particles were estimated under a stereomicroscope at 40Â magnification. We distinguished different types of charcoal morphotypes as in Colombaroli et al (2014). Grass cuticles usually occur in flat sheets, and epidermal cells are arranged in parallel rows, with stomata within the rows (Jensen et al, 2007), and mostly have a length to width ratio !…”
Section: Methodsmentioning
confidence: 99%
“…Leaf fragments can be separated from other charred material due to the presence of leaf veins, which are characterized by a divergence of the branches from a node (Jensen et al, 2007). Further details can be found in Beffa (2012) and Colombaroli et al (2014).…”
Section: Methodsmentioning
confidence: 99%
“…The sediment samples were wet sieved in a 150 µm mesh sieve. The residue was then soaked in 5 % metaphosphate solution followed by soaking in 8 % hydrogen peroxide solution for 12 hrs to concentrate charcoal particles and bleach all non-charcoal organic matter in the sediment (Stevenson and Haberle, 2005;Schlachter and Horn, 2010;Colombaroli et al, 2014). Washed samples were then scanned under a stereomicroscope at a magnification of 15x to identify and count the charcoal particles.…”
Section: Macro-charcoal Analysismentioning
confidence: 99%
“…An investigation from a South African savanna region reveals that these ecosystems historically alternated between grassland phases maintained by lower levels of water availability, herbivory and less frequent fire events and woody-savanna vegetation phases maintained by increased water availability, herbivore browsing of tree communities, and more frequent/ intense fires (Gillson and Ekblom, 2009). Such studies, which use multiple paleoecological and paleoclimatic proxies like stable isotope ratios of carbon and oxygen (Lisiecki and Raymo, 2005;West et al, 2006), charcoal (Gavin et al, 2007;Colombaroli et al, 2014) and herbivore dung fungal spores (Ekblom and Gillson, 2010;Baker et al, 2012) establish clear links between past climate, disturbance regimes and vegetation changes. However, the timing and magnitude of climatic and disturbance factors are variable across tropical grasslands globally, and further, the effects of these factors on vegetation are also variable, depending on whether systems are mesic or arid (Veldman et al, 2015).…”
mentioning
confidence: 99%